Elite Predatory Practices in the Budgeting Process of Local Development in Indonesia - Mahsun, Muhammad (Department of Political Sciences, Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2021)
This article analyses the pattern of relationships between local businessmen-politicians in parliament and the executive elite in budgeting for local infrastructure development. By using the theory of patronage, cronyism, and predatory state as a framework analysis, this paper provides a theoretical contribution that sees the three theories are complementary to each other. The predatory practices in Indonesia often work in the context of political patronage and cronyism. In this study, the businessmen-politicians in parliament and executive elites of local government placed as local-state actors relate to each other in the informal networks for the practices of a predatory state. My findings showed that the domination of the businessmen-politicians in local parliament has created a networks of patronage politics and cronyism with the executive elite. This is evidenced by some of the findings. First, the businessmen-politicians and the executive elites collaborated to hijack the budgeting process. Second, there has been a monopoly of tenders of local infrastructure development projects by the businessman-politicians in the local parliament. Third, the services were exchanged between the businessmen-politicians with the executive elite who are in a relationship of patronage and cronyism are public goods.